2020
DOI: 10.1017/jfm.2020.509
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on the leading-edge vortex formation and detachment mechanism of a pitching and plunging plate

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…The alternative positive/negative bands upstream of the LEV correspond to the secondary vortices that form near the leading edge of the wing (Li et al. 2020). Figures 11( a , b ) show that the LEV of the rigid case moves downstream at roughly the same velocity at both spanwise positions, and 0.6.…”
Section: Resultsmentioning
confidence: 99%
“…The alternative positive/negative bands upstream of the LEV correspond to the secondary vortices that form near the leading edge of the wing (Li et al. 2020). Figures 11( a , b ) show that the LEV of the rigid case moves downstream at roughly the same velocity at both spanwise positions, and 0.6.…”
Section: Resultsmentioning
confidence: 99%
“…The determination of this threshold is based on the work of Li et al. (2020). The position of the vortex centre is determined by the criterion proposed by Graftieaux, Michard & Nathalie (2001).…”
Section: Basic Flow Situation and Criterion Of Critical Momentsmentioning
confidence: 99%
“…Li et al. (2020) found that with the change in the maximum effective angle of attack, different secondary vortex structures lead to the shedding of DSV. Li et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the original airfoil, the connection between the leading edge shear layer and the DSV is weaker for the TEF airfoil (Figure 18(d)). When the connection between the leading edge shear layer and the DSV is weak, it means that the DSV no longer accumulates vorticity from the leading edge shear layer [27]. Due to the lack of vorticity supply from the leading edge shear layer, the strength of the DSV decreases rapidly.…”
Section: Analysis Of the Circulation And Vortexmentioning
confidence: 99%